2020
DOI: 10.1016/j.bbih.2020.100071
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid acts as an agonist of the dopamine D2L receptor, regulates immune responses, and ameliorates experimentally induced colitis in mice

Abstract: Tannic acid (TA) is an herbal polyphenol containing a galloyl group that has been prescribed to treat gastroenteritis, diarrhea, and irritable bowel syndrome. TA has anti-inflammatory, anti-cancer, and anti-viral properties; however, the molecular mechanisms of these potential therapeutic effects are still largely unknown. Here, we examined the ability of TA to induce anti-inflammatory responses. TA was found to be an agonist of the dopamine D2L receptor. TA reduced interferon (IFN)-γ and interleukin (IL)-1β s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
3
5
0
Order By: Relevance
“…[46][47][48] It has been reported that administering dopamine or activating dopamine D2L receptors could reduce secretion of IFN-γ. 49,50 Our results are consistent with this, as a correlation analysis showed that IFN-γ was negatively correlated with dopamine (r = −0.981). Stimulation of dopamine D3 receptors (D3R) reduced mast cell activation and inhibited IL-13 release in the mouse gut, which correlated significantly and negatively with the results of our correlation analysis between DA in brain and IL-13 in skin (P < 0.05, r = −0.960).…”
Section: Discussionsupporting
confidence: 89%
“…[46][47][48] It has been reported that administering dopamine or activating dopamine D2L receptors could reduce secretion of IFN-γ. 49,50 Our results are consistent with this, as a correlation analysis showed that IFN-γ was negatively correlated with dopamine (r = −0.981). Stimulation of dopamine D3 receptors (D3R) reduced mast cell activation and inhibited IL-13 release in the mouse gut, which correlated significantly and negatively with the results of our correlation analysis between DA in brain and IL-13 in skin (P < 0.05, r = −0.960).…”
Section: Discussionsupporting
confidence: 89%
“…We also showed previously that tannic acid is a D2-like receptor agonist, and that tannic acid suppressed IL-17 production in chemically induced colitis models (19). More recently, we determined that tannic acid inhibited alveolar bone resorption in a carrageenan-induced rat model of periodontitis (20).…”
Section: Ropinirole Inhibits Inflammatory Cytokine Production In Ging...mentioning
confidence: 61%
“…HT have been shown to contribute to declining of ROS formation, suppressing the nuclear factor kappa‐B (NF‐κB) pathway, and inhibiting the expression of proinflammatory mediators by immune cells in multiple disease models of mice induced by lipopolysaccharide (LPS). These disease models include neuroinflammation, colitis, depressive‐like behaviors, acute lung injury, and septic heart injury (Kawano et al, 2020; Luduvico et al, 2020; Sivanantham, Pattarayan, Rajasekar, et al, 2019). In vitro studies also suggested that HT mainly alleviated inflammatory response by reducing the inflammatory cytokines and inhibiting ROS production in cells (Wu et al, 2019; Yang et al, 2021).…”
Section: Hydrolysable Tanninsmentioning
confidence: 99%